Local ecological knowledge also comes "from books": cultural change, landscape transformation and conservation of biodiversity in two natural protected areas from Portugal - Carvalho, Ana Maria (2011)
Resumo publicado de comunicação oral apresentada na 10th EASA Biennial Conference: Ljubljana, Slovenia